Behandlungspfade in der Versorgung von Patienten mit Schizophrenie und Depression = Treatment pathways in the care of patients with schizophrenia and depression - Salize, Hans Joachim (Der Nervenarzt, 2015)
SummaryBackgroundIn mental healthcare the concept of pathways addresses diverse issues and problem areas, such as heterogeneous health service offers, the regional variability of treatment concepts and clear-cut guidelines on how and where to obtain treatment for a particular mental disorder. The ambiguous aspects of the concept require international and national definitions and consensus which must also cover quality criteria.MethodsThis article gives an overview of currently available evidence for the analysis of clinical pathways and pathways to care in international mental healthcare, covering studies on schizophrenia and depression from 2010 to 2014. Results and discussionThe ambiguity of the concept impedes the overview and does not provide unequivocal results. The development, implementation and analyses of guidelines or clear-cut clinical and pathways to care must consider individual, clinical and care system aspects as well as the interplay of these factors. Results suggest that system aspects tend to dominate over clinical factors of schizophrenia and depression. As a consequence, the definition, implementation and evaluation of clinical pathways or pathways to mental healthcare is first and foremost a responsibility of the respective national mental healthcare system and must be understood on that level, before findings are summarized internationally and models of best practice are debated.